Etiological shifts and clinical outcomes of acute pancreatitis between urban and rural areas: evidence from a 20-year retrospective database - Cao, Ximei; Liu, Zide; Rao, Jingwen; Wu, Jie; Huang, Xin; Xia, Liang; Luo, Lingyu; Shu, Xu; Zhu, Yin; Lu, Nonghua; He, Wenhua (Frontiers in Medicine, 2025)
BackgroundAcute pancreatitis (AP) is a well-recognized digestive emergency with established clinical significance. However, current evidence regarding urban–rural distribution patterns of AP patients remains relatively limited. Through large-scale data analysis, this study aims to provide preliminary epidemiological references for this understudied area.MethodsThis 20-year retrospective cohort study (2005–2024) analyzed 12,214 acute pancreatitis (AP) cases from a tertiary medical center to investigate urban–rural disparities in etiology and clinical outcomes. Patients were stratified into urban (n = 5,002) and rural (n = 7,212) groups based on residential location. We compared demographic characteristics, etiological distributions, disease severity, complications, and hospitalization outcomes between the groups. Risk factors for moderate-to-severe AP were assessed using multivariable logistic regression, with adjustment for demographic, clinical, and temporal covariates.ResultsUrban patients exhibited a rising burden of hypertriglyceridemia-induced AP (HTG-AP; 30.6% vs. rural 26.3%, p < 0.001), surpassing biliary AP as the dominant etiology by 2023, while rural populations maintained higher biliary AP prevalence (56.4% vs. 51.7%, p < 0.001). Rural patients demonstrated prolonged symptom-to-admission intervals (median 3 vs. 2 days), elevated APACHE II scores (8 vs. 7), and increased severe AP incidence (20.7% vs. 18.3%, p < 0.01), with higher risks of infected pancreatic necrosis (5.3% vs. 4.3%) and abdominal compartment syndrome (1.7% vs. 1.1%). Multivariable analysis suggested that rural group may be associated with increased risk of moderate-to-severe AP (aOR = 1.13, p = 0.005), alongside hypertriglyceridemia (aOR = 2.06) and delayed admission (aOR = 1.01/day). Temporal trends revealed accelerated HTG-AP growth post-2020 in both groups, paralleling metabolic syndrome escalation.ConclusionThese findings underscore the imperative for dual interventions: urban-focused metabolic risk mitigation and rural-targeted biliary disease management, informed by evolving etiological landscapes.